PERENCANAAN LONG STORAGE JETIS KEC BLORA KAB BLORA - Eka Cahyaningsih; Rahayu Cahyaning Ratri; Dwi Kurniani; Hary Budieny (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2016)
Floods are natural disasters that regularly occur in DAS Lusi during the rainy season. Reduced water catchment areas in the upstream area of the river is one of the causes of increased flood discharge in river Lusi. Attempts to reduce it is to plan long storage system, a building that utilizes water as a resevoir riverwith weir building in the downstream.Long storage will be built on the upstream of the Lusi, located at Jetis, Kecamatan Blora, Kabupaten Blora. The purpose of the construction of long storage Jetis is a flood control system and as a resevoir for the surrounding areas. From the result of rainfall data in Blora, Jiken, Jepon, Bogorejo and Tempuran station, return period of 25 years Q25 = 242.059 m3 / sec are used to analyze the capacity of the river and weir stability. While the discharge is used in analyzing the resevoir using a debit andalan based formula FJ Mock with large long storage bin is 42 liters / sec.Plan development time required was 12 weeks with a total budget of Rp. 12,852,198,000.00. (Twelve billion eight hundred and fifty-two million one hundred ninety eight thousand rupiah).